2017
DOI: 10.2134/agronj2016.03.0174
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Diverse Cover Crop Mixtures: Effects of Planting Date and Seeding Rate

Abstract: Cover crop mixtures retain higher diversity when allowed sufficient growth in fall. Cereal rye dominates mixtures in spring, particularly when fall planting is delayed. Grasses overperform in cover crop mixtures compared to their growth in monoculture. Brassicas underperform in cover crop mixtures compared to their growth in monoculture. Legumes’ growth in cover crop mixtures varies depending on species and planting time. Cover crop mixtures may provide greater diversity of benefits than monocultures. To devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 35 publications
7
89
0
Order By: Relevance
“…Notably, more functionally diverse mixtures increased multifunctionality by ameliorating disservices associated with component species, not by enhancing services. In this study, cereal rye was included in all mixtures and comprised 20 to 40% of fall and 70 to 90% of spring aboveground biomass (Murrell et al, 2017). Rye was exceptional in providing services in the biomass bundle, but it had high disservice scores for the nutrient bundle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, more functionally diverse mixtures increased multifunctionality by ameliorating disservices associated with component species, not by enhancing services. In this study, cereal rye was included in all mixtures and comprised 20 to 40% of fall and 70 to 90% of spring aboveground biomass (Murrell et al, 2017). Rye was exceptional in providing services in the biomass bundle, but it had high disservice scores for the nutrient bundle.…”
Section: Discussionmentioning
confidence: 99%
“…From 2012 to 2015 on land transitioning to organic certification in Rock Springs, PA (40°43ʹ N, 77°55ʹ W), 10 cover crop treatments (Table 1) and a no‐cover crop control (hereafter, “control”) were planted after wheat ( Triticum aestivum L.) and terminated prior to planting maize ( Zea mays L.; Murrell et al, 2017). We quantified eight ecosystem services provided by cover crops for three consecutive years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murrell et al. () found that fodder radish performed better in monoculture than in mixture. Oilseed radish has high weed suppressive ability (Sturm, Kunz, Peteinatos, & Gerhards, ), but a negative aspect of oilseed radish is its ability to host the pathogen Plasmodiophora brassicae , which causes the disease clubroot in some Brassicaceae species, for example oilseed rape ( Brassica napus ) (Wallenhammar, Almquist, Söderström, & Jonsson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Danish field experiments have found that fodder radish has greater above-ground biomass production and N uptake than other commonly used cover crops as perennial ryegrass, chicory (Cichorium intybus), dyer′s woad (Isatis tinctoria) (Munkholm & Hansen, 2012;Sapkota et al, 2012) and winter rye (Secale cereale) (Thorup-Kristensen, 1994). Murrell et al (2017) found that fodder radish performed better in monoculture than in mixture. Oilseed radish has high weed suppressive ability (Sturm, Kunz, Peteinatos, & Gerhards, 2017), but a negative aspect of oilseed radish is its ability to host the pathogen Plasmodiophora brassicae, which causes the disease clubroot in some Brassicaceae species, for example oilseed rape (Brassica napus) (Wallenhammar, Almquist, Söderström, & Jonsson, 2012).…”
Section: Introductionmentioning
confidence: 99%